Psychometric Properties of the Italian Mentalization Questionnaire: Assessing Structural Invariance and Construct Validity. Issue 5 (3rd September 2022) - Raimondi, Giulia; Samela, Tonia; Lester, David; Imperatori, Claudio; Carlucci, Leonardo; Contardi, Anna; Balsamo, Michela; Innamorati, Marco
Abstract: Mentalization is an important interpersonal ability, necessary for adaptive interpersonal relationships and emotion regulation. Deficits in mentalization have been associated with poor psychological outcomes and have been observed in patients with Borderline Personality Disorder. The Mentalization Questionnaire (MZQ) has been developed as self-report measure of mentalization deficit. The aim of the study was to investigate the dimensionality of the MZQ in a nonclinical sample composed of Italian adults from the general population and to analyze its performance in categorizing individuals with higher risk of borderline symptoms. A non-clinical sample of 1, 015 adults (709 women and 306 men) was administered the Italian versions of the MZQ, the Reflective Functioning Questionnaire (RFQ), and a measure of borderline psychopathology. A revised single-factor solution fitted the data well and demonstrated metric invariance across gender. The internal consistency (Ordinal α  = 0.87) and stability ( r  = 0.84) were satisfactory. The MZQ was moderately associated with the RFQ dimensions. The ROC curve analysis showed that the MZQ was able to discriminate satisfactorily people with higher risk for borderline symptomatology from those with lower risk. The MZQ may, therefore, be considered a reliable and valid measure of mentalization for categorizing people at higher risk for borderline pathology.